Real-time torque behavior of reciprocating nickel–titanium instruments using different irrigating solutions - Uğur Dursun; Mevlüt Sinan Ocak (PLoS ONE, 2026)
Reciprocating nickel–titanium instruments generate mechanical stress during root canal preparation, which may affect instrument safety. Although instrument design is known to influence torque generation, the effect of different irrigating solutions on the real-time operative torque remains unclear. This study aimed to investigate the impact of various irrigating solutions on torque generated during root canal shaping using reciprocating single-file systems. Extracted human mandibular premolars with oval canals were assigned to groups prepared using sodium hypochlorite, ethylenediaminetetraacetic acid, or saline in combination with three reciprocating file systems. All canals were instrumented with a torque-controlled motor, and the real-time operative torque and preparation time were digitally recorded. The mean torque, maximum torque, and shaping duration were statistically compared between the irrigant and instrument groups. The irrigation solution alone did not show a significant main effect on torque values or preparation time. However, a significant interaction between the file system and irrigant type was detected, indicating that the torque response depended on the specific file–irrigant combination. In contrast, the file system type significantly influenced torque behavior, with the T-Endo MUST system producing higher mean and peak torque than the other instruments. These findings suggest that instrument design characteristics may have a greater impact on the development of mechanical stress during root canal preparation than the irrigation solution used.